SUMMARY OF THE ADVISORY OPINION OF THE INTERNATIONAL COURT OF JUSTICE (ICJ) DATED 23 JULY 2025 - Haydar Celik, Nuran (International Scientific Journal Vision, 2025)
This article provides a comprehensive summary of the International Court of Justice’s (ICJ) advisory opinion on the obligations of states concerning climate change, issued on 23 July 2025. The ICJ recognizes climate change as an existential threat and affirms binding legal duties of states under both treaty and customary international law. These duties include emission reductions, adaptation measures, regulation of private actors, and support for vulnerable countries. The Court emphasizes the principle of due diligence, international cooperation, and the human right to a clean, healthy, and sustainable environment. Furthermore, the opinion clarifies state responsibility for climate-related harm and outlines the framework for remedies under international law. This study aims to evaluate the key and significant determinations of the decision from an international law perspective paragraph by paragraph and to briefly present the obligations outlined by the court along with their sources, as well as the responsibilities arising therefrom.